PEMANFAATAN SALEP DAUN BINAHONG (Basella rubra linn) SEBAGAI OBAT ALTERNATIF LUKA TERBUKA - Nurrafi Wira Syahputra; Farhan Dwi Aldisa; Safira Rohdotul Mauluddiyah; Fira Hazmi Fardani; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
The large number of wound medicines that contain various kinds of chemicals that have side effects at high prices has caused people to think twice about using these drugs. The leaves of the binahong plant contain flavonoids which function to prevent microbial growth and contain saponins which function to stimulate the formation of collagen, a protein that plays a role in wound healing. Binahong plants are easily available and abundant in natural, so there is a need for research on the leaves of the binahong plant as a medicine for open wounds. The process of healing open wounds uses binahong ointment and two other wound medicines as a comparison, namely betadine and sulfanilamit powder. Wound healing using betadine by dripping betadine into open wounds. While the wound healing process uses binahong leaf ointment by processing binahong leaves into ointment. Then apply the processed binahong leaf ointment to the open wound. And the healing process uses sulfanilamine powder by sprinkling it on the open wound. The stages of wound healing include inflammation or inflammation, proliferation, namely cell regeneration, and termination. Open wounds will heal quickly if given substances that inhibit bacterial growth and can stimulate the formation of collagen, namely flavonoids and saponins. After obtaining data from the results of a comparison between healing open wounds with betadine, binahong ointment and sulfanilamit powder, the data were then analyzed. Using betadine, wounds can heal for 5 days, using binahong ointment can heal for 4 days, and using sulfanilamine powder can heal for 6 days. Binahong leaf ointment heals faster than betadine and sulfanilamit powder, because binahong leaf ointment contains flavonoids and saponins. In addition, at an affordable price, you can get an ointment with a larger volume compared to other wound medicines. After conducting research, it can be concluded that binahong leaf ointment is feasible to be used as an effective alternative medicine for open wounds. Keywords: Binahong Leaves, Ointments, and Open Wounds